Etiological Spectrum and Outcome of Pleural Effusion in Children: A Hospital-Based Study from Bangladesh (Northern International Medical College Journal, 2025)
Background: Pleural effusion is a frequent cause of respiratory morbidity in children, with variable etiology and outcomes depending on geography, vaccination status, and underlying diseases and timely management. Methods: This prospective observational study was conducted in the department of Respiratory Medicine of Bangladesh Shishu Hospital and Institute, enrolling 511 consecutive children diagnosed radiologically as pleural effusion between January 2022 and June 2024. Clinical features, imaging findings and pleural fluid analyses including cytology, biochemistry, microbiology, Gene Xpert, adenosine deaminase (ADA), lactate dehydrogenase (LDH) and immunochromatographic test (ICT) for Streptococcus pneumoniae were performed for all patients. Data was analyzed descriptively using SPSS v24. Results: Among the children enrolled total 218 (42.7%) were aged 5–